The Study of Morphology, Phytochemical, and Distribution of Pittosporum moluccanum in Mount Merbabu National Park (TNGM)For the Development of Educationl Teaching Materials - Setiyarini, Chatarina Titik; Kristiani, Elizabeth Betty Elok; Yulianto, Sri (International Journal of Active Learning, 2020)
This study aims to 1) observe the morphology of P. moluccanum, 2) analyze the content of chemical compounds in P. moluccanum, and 3) determine Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI) of P. moluccanum. The research was conducted in the form of morphology studies by conducting field studies, phytochemical compounds sample test by conducting sample preparation, chemical screening, and detection of aromatic compounds and quercetin, and remote sensing of Landsat 8.0 OLI satellite imagery. The results of morphological studies show that P. moluccanum have the same characteristics as plants in the literature, whereas the phytochemical test shows that P. moluccanum’s leaves and fruit contain flavonoids, tannins, saponins, steroids, and alkaloids. These compounds are known to have many functions for medicines. NIR analysis shows that leaf and fruit samples are detected to have aromatic compounds (essential oils) which are widely used as raw materials for fragrance oils or cosmetics. The results of remote sensing using NDVI in the Selo region, Boyolali produce a maximum vegetation index value of 0.464, meaning that the area has a high level of greenness, while the EVI used to see the level of health and fertility of plants in August 2018 shows the same figure, which is 0.464, meaning that the plant is in healthy condition. Remote sensing with satellite imagery helps analyze the distribution of sample plants in a large area. The results of this study can be used as a development of teaching materials both at junior and senior high school levels.